Distinguishing between Knowledge Gaps and Misconceptions of Alzheimer’s Disease among Caregivers in the UK - Petra, M. J. Pollux; Victoria, Elliot; Mark, Howard; John, M. Hudson (Journal of Aging Research And Healthcare, 2016)
A popular scale for assessing knowledge about Alzheimer’s disease is the Alzheimer’s Disease Knowledge Scale (ADKS). The aim of the study was to investigate the effect of adding ‘don’t know’ to the original ‘true’ or ‘false’ response option. It was assumed that this modification would provide insight into the reasons underlying incorrect responses and could distinguish between misconceptions and knowledge gaps. To investigate this, carers (care home carers and informal carers) and members of the general population were recruited. The results showed that percentage correct responses was lower than previously reported, suggesting potential inflation of knowledge by guesses without the ‘don’t know’ option. Moreover, care-home workers were more likely to select the incorrect response than ‘don’t know’ compared to informal carers for several items related to the earlier stages of AD, suggesting a higher level of misconceptions around this topic and highlighting potential training needs for care home carers.
Keywords: ADKS; knowledge; misconceptions; knowledge gaps; formal carers; informal carers.